Quantification of endogenous levels of IAA, IAAsp and IBA in micro-propagated shoots of hybrid chestnut pre-treated with IBA - Gonçalves, José Carlos (2013)
Endogenous levels of indole-3-acetic acid (IAA), indole-3-acetylaspartic acid (IAAsp) and indole-3-butyric acid (IBA) were measured during the first 8 d of in vitro rooting of rootstock from the chestnut ‘M3’ hybrid by high performance liquid chromatography (HPLC). Rooting was induced either by dipping the basal ends of the shoots into a 4.92-mM IBA solution for 1 min or by sub-culturing the shoots on solid rooting medium supplemented with 14.8- μM IBA for 5 d. For root development, the induced shoots were transferred to auxin-free solid medium. Auxins were measured in the apical and basal parts of the shoots by means of HPLC. Endogenous levels of IAA and IAAsp were found to be greater in IBA-treated shoots than in control shoots. In extracts of the basal parts of the shoots, the concentration of free IAA showed a significant peak 2 d after either root inductive method and a subsequent gradual decrease for the remainder of the time course. The concentration of IAAsp peaked at day 6 in extracts of the basal parts of shoots induced with 14.8-μM IBA for 5 d, whereas shoots induced by dipping showed an initial increase until day 2 and then remained stable. In extracts from basal shoot portions induced by dipping, IBA concentration showed a transient peak at day 1 and a plateau between day 2 and 4, in contrast to the profile of shoots induced on auxin-containing medium, which showed a significant reduction between 4 and 6 d after transferred to auxin-free medium. All quantified auxins remained at a relatively low level, virtually constant, in extracts from apical shoot portions, as well as in extracts from control non-rooting shoots. In conclusion, the natural auxin IAA is the signal responsible for root induction, although it is driven by exogenous IBA independently of the adding conditions.